Survey of Object Tracking Algorithm Based on Siamese Network. Issue 1 (1st February 2022) - Zuo, Mengle; Zhu, Xuyang; Chen, Yongchao; Yu, Junyang
Abstract: The network model using deep learning have been widely used in the sphereof visual object tracking for the past few years. The Siamese network can utilize the model based on deep learning to achieve a balance between the tracking accuracy and speed in the visual object tracking. This work mainly introduces the development process of the visual target tracking field and traditional target tracking algorithms. It focuses on the Siamese network structure and the improved the Siamese algorithm, and compares tracking results of related algorithms. Aiming at the deficiencies of existing Siamese object tracking algorithms, the future development trend is prospected.